(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Application of the Group Investigation Model to Improve the Ability to Understand the Unity of NKRI in Learning civics. This study aims to determine whether the application of the Group Investigation type cooperative learning model can the ability to understand the integrity of the NKRI on Class V.B SD Negeri 13 Palembang students in the odd semester of the 2017/2018 school year. The subject of the action referred to in this study were the students of Class V.B of SD Negeri 13 Palembang, which amounted to 38 students. Learning completeness increases from cycle I, to cycle II namely 73, 68% and 86.84% In the second cycle classical student mastery learning has been achieved and has improved very well. Keywords: Civics, Group Investigation (GI), NKRI. Abstrak: Penerapan Model Group Investigation Untuk Meningkatkan Kemampuan Memahami Keutuhan NKRI Dalam Pembelajaran Pkn. Penelitian ini bertujuan untuk mengetahui apakah penerapan model pembelajaran koopertif tipe Group Investigation dapat kemampuan memahami keutuhan NKRI PKn pada peserta didik Kelas V.B SD Negeri 13 Palembang semester ganjil tahun pelajaran 2017/2018. Subjek yang dimaksud tindakan dalam penelitian ini adalah peserta didik Kelas V.B SD Negeri 13 Palembang yang berjumlah 38 peserta didik. Ketuntasan belajar meningkat dari siklus I, ke siklus II yaitu 73,68% dan 86,84% Pada siklus II ketuntasan belajar siswa secara klasikal telah tercapai dan mengalami peningkatan yang sangat baik. Kata Kunci: PKn, Group Investigation (GI), NKRI.